An Investigation Into the Disease Profile and Healthcare Costs of Inpatients Treated at a Major Oral and Maxillofacial Surgical Center. Issue 7 (October 2016) - Yang, Yue; Zhang, Yi; Li, Peijun; Jiang, Ying; Yang, Guoyong
Abstract : Objective: This study is a retrospective review which reported on the treatment records of oral and maxillofacial inpatients treated at a medical institution with the largest scale of oral and maxillofacial specialist services in China, to reflect on disease profile, healthcare model characteristics and the medical status of oral and maxillofacial surgery in China. Patients and Methods: Information on 25, 825 patients hospitalized between 2008 and 2013 was collected to analyze the mean length of stay (LOS) and preoperative LOS, expenditure patterns, and payment status. Results: The overall mean LOS and preoperative LOS were 10.0 ± 4.9 days and 4.3 ± 2.1 days, respectively. The main costs composed of surgery charges and material costs (47.4%). The proportion of nonlocal patients was 76.34% and the majority of patients used their basic medical insurance (57.74%), and the proportion of patients self-paying showed the largest increase over time. Rising charges for inpatients in this institution did not cause an aggravation of medical cost burden of residents. Cost burden of oral and maxillofacial malignancy surgery patients was higher than in developed countries. Conclusions: The overall mean LOS and preoperative LOS were higher than that of similar patients globally. Compared with medicine and material costs, medical income is lower and the value of medical personnel labor is not fully appreciated. The proportion of patients who actually enjoy the benefits of the basic medical insurance in China is lower than the coverage.